Response of the Eastern Mediterranean Microbial Ecosystem to Dust and Dust Affected by Acid Processing in the Atmosphere - Krom, Michael D.; Shi, Zongbo; Stockdale, Anthony; Berman-Frank, Ilana; Giannakourou, Antonia; Herut, Barak; Lagaria, Anna; Papageorgiou, Nafsika; Pitta, Paraskevi; Psarra, Stella; Rahav, Eyal; Scoullos, Michael; et al. (Frontiers in Marine Science, 2016)
Acid processes in the atmosphere, particularly those caused by anthropogenic acid gases, increase the amount of bioavailable P in dust and hence are predicted to increase microbial biomass and primary productivity when supplied to oceanic surface waters. This is likely to be particularly important in the Eastern Mediterranean Sea (EMS), which is P limited during the winter bloom and N&P co-limited for phytoplankton in summer. However, it is not clear how the acid processes acting on Saharan dust will affect the microbial biomass and primary productivity in the EMS. Here, we carried out bioassay manipulations on EMS surface water on which Saharan dust was added as dust (Z), acid treated dust (ZA), dust plus excess N (ZN) and acid treated dust with excess N (ZNA) during springtime (May 2012) and measured bacterioplankton biomass, metabolic and other relevant chemical and biological parameters. We show that acid treatment of Saharan dust increased the amount of bioavailable P supplied by a factor of ~40 compared to non-acidified dust (18.4 nmoles P mg-1 dust vs. 0.45 nmoles P mg-1 dust, respectively). The increase in chlorophyll, primary and bacterial productivity for treatments Z and ZA were controlled by the amount of N added with the dust while those for treatments ZN and ZNA (in which excessive N was added) were controlled by the amount of P added. These results confirm that the surface waters were N&P co-limited for phytoplankton during springtime. However, total chlorophyll and primary productivity in the acid treated dust additions (ZA and ZNA) were less than predicted from that calculated from the amount of the potentially limiting nutrient added. This biological inhibition was interpreted as being due to labile trace metals being added with the acidified dust. A probable cause for this biological inhibition was the addition of dissolved Al, which forms potentially toxic Al nanoparticles when added to seawater. Thus, the effect of anthropogenic acid processes in the atmosphere, while increasing the flux of bioavailable P from dust to the surface ocean, may also add toxic trace metals such as Al, which moderate the fertilizing effect of the added nutrients.